Enhancing English Language Skills for Computer Students through Presentations - Rifiyanti, Hafizah; Hardianti, Hardianti (English Education Study Program, 2023)
Presentation affects the development of English-speaking skills because it requires good and fluent English-speaking skills. In fact, many students are not motivated to perform in-class presentations, especially using English. The study was conducted with the aim of evaluating the effectiveness of a presentation-based language learning approach The study was conducted using a survey design. The data is collected from 36 sample computer students through questionnaires. Interpreting the result of questionnaires and drawing conclusions is the way to analyze the data. Based on the results and findings, recommendations are made for how presentations can be used to enhance the English language skills of computer students are generally interested in and motivated by presentations to improve their English language skills. The majority of respondents stated that they were motivated to attend such presentations, and all agreed that they had gained a better understanding of the technical terms of computer science. For further improvement, there were various opinions on how the presentations could be improved to better enhance English language skills